ӘЖИНИЯЗДЫҢ БАБАЛАРЫ КИМ БОЛҒАН?, БУЛ ҲАҚҚЫНДА БИЗ НЕ БИЛЕМИЗ?... - Есебаев, М.М. (SCIENCE and SOCIETY, 2025)
The article reflects the results of research on the origin and ancestors of the son of Ajiniyaz Kosiboy. These research works are a great innovation in the history of Karakalpak literature.
Keywords: history; ethnography; genealogy; madrasa; moaque; ahun; eshon